Three methods of delivering clinic-based training on syndromic management of sexually transmitted diseases in South Africa: a pilot study. (1st October 2015) - Weaver, Marcia R; Pillay, Erushka; Jed, Suzanne L; de Kadt, Julia; Galagan, Sean; Gilvydis, Jennifer; Marumo, Eva; Mawandia, Shreshth; Naidoo, Evasen; Owens, Tamara; Prongay, Vickery; O'Malley, Gabrielle
Abstract : Introduction: The South African National Department of Health sought to improve syndromic management of sexually transmitted infections (STIs). Continuing medical education on STIs was delivered at primary healthcare (PHC) clinics using one of three training methods: (1) lecture, (2) computer and (3) paper-based. Clinics with training were compared with control clinics. Methods: Ten PHC clinics were randomly assigned to control and 10 to each training method arm. Clinicians participated in on-site training on six modules; two per week for three weeks. Each clinic was visited by three or four unannounced standardised patient (SP) actors pre-training and post-training. Male SPs reported symptoms of male urethritis syndrome and female SPs reported symptoms of vaginal discharge syndrome. Quality of healthcare was measured by whether or not clinicians completed five tasks: HIV test, genital exam, correct medications, condoms and partner notification. Results: An average of 31% of clinicians from each PHC attended each module. Quality of STI care was low. Pre-training (n=128) clinicians completed an average of 1.63 tasks. Post-training (n=114) they completed 1.73. There was no change in the number of STI tasks completed in the control arm and an 11% increase overall in the training arms relative to the control (ratio of relative risk (RRR)=1.11, 95% CI 0.67 to 1.84). Across training arms, there was a 26% increase (RRR=1.26, 95% CI 0.77 to 2.06) associated with lecture, 17% increase (RRR=1.17, 95% CI 0.59 to 2.28) with paper-based and 13% decrease (RRR=0.87, 95% CI 0.40 to 1.90) with computer arm relative to the control. Conclusions: Future interventions should address increasing training attendance and computer-based training effectiveness. Trial registration number: AEARCTR-0000668.